2015
DOI: 10.17987/icfj.v2i1.83
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular calcification and bone: a comparison of the effects of dietary and serum antioxidants

Abstract: <p>Severe cardiovascular (CV) calcification can manifest as fully formed bone and is regularly found with osteoporosis; both have been shown to be associated with oxidative stress. Studies of the effect of antioxidants on CV calcification are few, but show that deficiency can induce both CV calcification and bone loss, while in conditions of oxidative stress such as renal failure, diabetes and smoking or in osteoporosis and fracture, antioxidants can reduce CV calcification and improve bone. The benefit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 118 publications
0
2
0
Order By: Relevance
“…MI is a complicated, multifactorial, and polygenic cardiovascular disease that results from the interplay between inherited predisposition and ecological factors [ 12 ]. Conventional risk aspects, such as nutrition, adiposity, insulin resistance, high blood pressure, hyperlipidemia, inflammatory processes, tobacco smoking, and excessive alcohol intake, have been shown to predict about 50% of an individual patient’s risk of having a cardiovascular incident, with the remainder due to genetic variables [ 13 , 14 , 15 ]. The genetic vulnerability may result from alteration and mutations in a number of genes, primarily those implicated in the clotting of blood, maintenance of blood pressure and metabolism of lipid, glucose, and homocysteine [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…MI is a complicated, multifactorial, and polygenic cardiovascular disease that results from the interplay between inherited predisposition and ecological factors [ 12 ]. Conventional risk aspects, such as nutrition, adiposity, insulin resistance, high blood pressure, hyperlipidemia, inflammatory processes, tobacco smoking, and excessive alcohol intake, have been shown to predict about 50% of an individual patient’s risk of having a cardiovascular incident, with the remainder due to genetic variables [ 13 , 14 , 15 ]. The genetic vulnerability may result from alteration and mutations in a number of genes, primarily those implicated in the clotting of blood, maintenance of blood pressure and metabolism of lipid, glucose, and homocysteine [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The association between both pathologies also depends on the mechanisms involved in the regulation of bone and CV metabolism 5 . We have previously shown that the nutrients and micronutrients that benefit the CV system generally also benefit bone [6][7][8] . In this article we discuss the effect and interactions of the principal dietary bone minerals (calcium, phosphorus, magnesium) and vitamin D on CV calcification and bone health in principally older adults.…”
Section: Introductionmentioning
confidence: 99%